Analysis of collaborative innovation behaviour and its influencing factors in scientific research crowdsourcing platforms: based on the fsQCA method - Jiajun Cao; Yuefen Wang; Xin Xie; Yuanzhi Lv; Peng Chen (Information Research: An International Electronic Journal)
Introduction. This study aims to explore the influencing factors and their combined effects on the benefits of knowledge innovation, and to explore the impact of factors on the effects of knowledge innovation from a configuration perspective.